ANALISIS KEPUASAN MAHASISWA TERHADAP KUALITAS PELAYANAN DI UNIVERSITAS BATANGHARI - M. Zahari MS (Jurnal Ilmiah Universitas Batanghari Jambi, 2013)
Student satisfaction is the result (outcome) over its perceived merit, equal or exceed desired expectations. Services at the University of Batanghari ideally more polite, fast and accurate. This means that the service orientation at the University of Batanghari must be based on student needs.The study was conducted to determine the level of student satisfaction with quality of services at the University of Batanghari (UNBARI), look for the determinants of satisfaction and are the dominant factors of service quality and seek UNBARI indicators making up the dominant factor. Data obtained by randomly distributing questionnaires to students 100 students are active in the sample.Data were analyzed using descriptive analysis and factor analysis to obtain a description of the factors that affect student satisfaction on the quality of services provided UNBARI. The results showed that there were 3 deminsi quality of service that is Reliability, Confidence, Emphaty, has been able to satisfy students. While deminsi Responsiveness and Tangibles, are still inadequate or unsatisfactory student because the score is categorized quite satisfied. In general, students were satisfied with the services provided by UNBARI.Keywords: Satisfaction, Quality of Service, Educational Services